Comparative epidemiology of influenza A and B viral infection in a subtropical region: a 7-year surveillance in Okinawa, Japan. Issue 1 (December 2016) - Iha, Yoshikazu; Kinjo, Takeshi; Parrott, Gretchen; Higa, Futoshi; Mori, Hideaki; Fujita, Jiro
Abstract Background The epidemic patterns of influenza B infection and their association with climate conditions are not well understood. Influenza surveillance in Okinawa is important for clarifying transmission patterns in both temperate and tropical regions. Using surveillance data, collected over 7 years in the subtropical region of Japan, this study aims to characterize the epidemic patterns of influenza B infection and its association with ambient temperature and relative humidity, in a parallel comparison with influenza A. Methods From January 2007 until March 2014, two individual influenza surveillance datasets were collected from external sources. The first dataset, included weekly rapid antigen test (RAT) results from four representative general hospitals, located in the capital city of Okinawa. A nation-wide surveillance of influenza, diagnosed by RAT results and/or influenza-like illness symptoms, included the age distribution of affected patients and was used as the second dataset. To analyze the association between infection and local climate conditions, ambient temperature and relative humidity during the study period were retrieved from the Japanese Meteorological Agency website. Results Although influenza A maintained high number of infections from December through March, epidemics of influenza B infection were observed annually from March through July. The only observed exception was 2010, when the pandemic strain of 2009 dominated. During influenza B outbreaks, influenza patients aged 5 to 9 years old and 10 to 14 years old more frequently visited sentinel sites. Although both ambient temperature and relative humidity are inversely associated with influenza A infection, influenza B infection was found to be directly associated with high relative humidity. Conclusion Further studies are needed to elucidate the complex epidemiology of influenza B and its relationship with influenza A. In the subtropical setting of Okinawa, epidemics of influenza B infection occur from March to July following the influenza A epidemic, and primarily affect school-age children. These findings help to define unknown aspects of influenza B and can inform healthcare decisions for patients located outside temperate regions.